PENGEMBANGAN APLIKASI HIKMAH DAN KEAJAIBAN AYAT-AYAT AL-QUR’AN BERBASIS ANDROID - Yayang Taopik; , Bunyamin; Asep Setia (Institut Teknologi Garut, 2015)
Aplikasi Hikmah dan Keajaiban Ayat-Ayat Al-Qur’an berbasis Android is application which developed to give an information and comprehension about meaning of Al-Qur’an verses related to science. Previously, Gustyawan have been designed an application called aplikasi fiqih ayat Al-Qur’an yang berkaitan dengan ilmu pengetahuan and several similar applications that already available at Google Play Store. in this research, to complete applications that already available before, it will be developed a simillar application which add some features that already not have such as audio files, online video links, and animation contents. Rasearch methodology in Pengembangan Aplikasi Hikmah dan Keajaiban ayat-ayat Al-Qur’an berbasis Android is using Prototype Development Method.